Laboratory Manual to accompany Chemistry In Context: Applying Chemistry To Society - A.Steehler Gail (McGraw -Hill, 2005)
The 5th edition Laboratory Manual that accompanies Chemistry in Context is compiled and edited by Gail Steehler (Roanoke College). The experiments use microscale equipment (wellplates and Beral-type pipets) as well as common materials. Project-type and cooperative/collaborative laboratory experiments are included. Additional experiments are available on the Online Learning Center, as is the instructor's guide.